Information Needs of Korean Immigrants in the United States: Selection and Use of Social Media - (:unkn) unknown (My University, 2023)
This mixed-method study investigates the information needs of Korean immigrants on social media and their selection and use of social media for finding information in the United States. The study was designed to answer six research questions: 1) What are the top types of information needs on social media that Korean immigrants fulfill during their everyday lives in the United States?; 2) What types of social media do Korean immigrants most frequently use during their everyday lives in the United States for different types of information needs?; 3) Are there any relationships between the types of social media Korean immigrants select and demographic factors, Information Communication Technology (ICT) experience level, cultural factors, and information needs?; 4) What factors influence the selection of types of social media among Korean immigrants?; 5) How do Korean immigrants use social media for finding information during their everyday lives in the United States?; 6) What factors influence Korean immigrants’ social media use for information seeking in their everyday lives in the United States? Data collection involved questionnaires, diaries, and interviews with 111 Korean immigrant participants completing questionnaires and 16 selected for diaries and interviews. Quantitative and qualitative methods, including descriptive statistic, Chi-square test of independence, and open coding, were used for analysis. In particular, descriptive analysis was utilized to identify education as the top information need on social media in RQ1. In RQ2, it was observed that Social Network Services (SNS) were most commonly used, while YouTube was popular for education, monitoring, and health information. The researcher investigated the relationship between social media types, demographic factors, ICT experience level, cultural factors, and information needs in RQ3 and revealed that there was a relationship between them by Chi-square test. In RQ4, the researcher identified factors influencing social media selection, such as social network influence, cultural preference, information needs, information quantity, and information format, using open coding. In RQ5, it was found that Korean immigrants primarily employed searching a keyword within a social media or clicking or subscribing to feeds/notifications to gather information. In RQ6, factors affecting social media use, such as algorithms, features, relevance of search results, and speed of information delivery, were identified. The study uncovered information needs among Korean immigrants and shed light on their predominant needs on social media. Moreover, the study presented a theoretical model for Korean immigrants' selection and use of social media platforms. It offered practical recommendations to cater to the information needs of Korean immigrants, such as algorithm optimization, improved search functionality, and language support. The study's limitations were acknowledged, and recommendations for future research were provided.
Keywords: Information needs; Information seeking; Korean immigrants; Mixed method; Social media